SYNTHESIS AND PHYSICAL-CHEMICAL PROPERTIESOF 3-ARIL-2-((3-(3-FLUORPHENYL)-1,2,4-TRIAZOLE-5-YL)THIO)PROP-2-EN-1-OLES - O. A. Bigdan; O. I. Panasenko; Ye. H. Knysh (Zaporozhye State Medical University, 2015)
Modern scientific schools, which search for new biologically active substances of synthetic nature, pay special attention to synthetic heterocyclic systems with nitrogenatom. Among these heterocyclic compounds, the derivatives of 1,2,4-triazole should be mentioned. Many publications of both domestic and foreign scientists show prospects on active molecules search on the field of 1,2,4-triazolessubstituted. Due to good solubility and wide range of biological activity, such derivatives have gained popularityamong scientists around the world. 1,2,4-triazoles overtheyearscauseparticularinterestfor synthetics chemistsandpharmacists. This isprimarily duetothewiderangeofbiologicalactivity, which representativesofthisclassof compoundsexhibit. Among these compounds there are derivatives containing in their structure aliphatic, aromatic and heterocyclic fragments. They have strong pharmacological properties due to spatial simulation and electronic characteristics of the active sites of natural compounds. Extensive development of organofluoric chemistrygainedin the last decade. Such intensive development of this industry is the result of demand for fluorinated compounds. Some of these compounds exhibit high biological activity, in particular, are active inhibitors of a number of enzymes and can be used aspesticides. The combinations of 1,2,4-triazole nucleus and some structural fragments of fluorophenylsubstituents can lead to molecules that have high biological effect, and sometimes form new, previously unknown types of pharmacological activity.Thus, the search for potential biologically active compounds requires constant modification of 1,2,4-triazoles structure and unifications under the methodology of their production, and the problem of development. Fluorophenylderivatives are relevant, have theoretical and practical significance. The aim of our work was to carry out the reduction reaction of fluorophenylderivatives of5-ilidentiazolo-[3,2-b]-1,2,4-triazoles-6-ones, which were obtained previously to investigate the physical and chemical properties of modern methods of product recovery analysis. Results. The authors fist investigated the reductionof 5-lidentiazolo- [3,2-b] -1,2,4-triazole-6-(5H)sodium borhydride-ones.It has been established that the reactions take place with the destruction of the thiazole-1,2,4-triazoles nucleus fragmentand form thecorresponding unsaturated alcohols. Structure and identity of derived molecules has been proved by modern physical-chemical methods of analysis. Finally, the structure has been confirmed by X-ray products recovery analysis.